2019
DOI: 10.1002/srin.201900105
|View full text |Cite
|
Sign up to set email alerts
|

Hot Temperature Mechanical Behavior of High‐Permeability 6.5 wt% Si Electrical Steel in a Mushy Zone

Abstract: Twin‐roll strip casting (TRSC) technology is successfully applied to obtain 6.5 wt% Si electrical steel (6.5 wt% Si steel) in a laboratory platform, although there are problems in the strip surface quality control restricting further industrial applications of the TRSC. Hot temperature mechanical behavior in the mushy zone associated with the cracking susceptibility of 6.5 wt% Si steel is studied using the Gleeble‐3800 simulation system in the temperature range of 1350–1435 °C and a strain rate of 3 s−1. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The conventional hot tensile (CHT) test after remelting the specimen has been widely used to determine the ZST, ZDT, as well as the mechanical properties of the solidifying steel. [ 3,21–23 ] In this method, the center part of a cylindrical sample, which usually has a diameter of around 10 mm and a length of around 100 mm, is heated by an induction coil or Joule‐resistant heater. The center part of the specimen is heated, melted, and solidified sequentially under a controlled thermal cycle.…”
Section: Introductionmentioning
confidence: 99%
“…The conventional hot tensile (CHT) test after remelting the specimen has been widely used to determine the ZST, ZDT, as well as the mechanical properties of the solidifying steel. [ 3,21–23 ] In this method, the center part of a cylindrical sample, which usually has a diameter of around 10 mm and a length of around 100 mm, is heated by an induction coil or Joule‐resistant heater. The center part of the specimen is heated, melted, and solidified sequentially under a controlled thermal cycle.…”
Section: Introductionmentioning
confidence: 99%
“…However, the brittle ordered phases (B2 and D0 3 ), which can be easily formed in the rolling processes of 6.5 wt% Si electrical steel, result in the near-zero plasticity of the material at room temperature. [2][3][4] In recent years, a large amount of research [5][6][7][8][9][10][11][12] has reported that certain alloying elements can effectively reduce the quantity of ordered phases in this steel and improve its plasticity. Moreover, our previous studies have found that an addition of 0.5 wt% Cu could facilitates successful production of 6.5 wt% Si electrical steel sheets in a laboratory via warm rolling.…”
mentioning
confidence: 99%